Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.2527/jas1986.633747x
|View full text |Cite
|
Sign up to set email alerts
|

Implanting Young Bulls with Zeranol from Birth to Four Slaughter Ages: III. Growth Performance and Endocrine Aspects2

Abstract: Seventy-two Simmental bull calves were assigned randomly either to a zeranol implanted (I) or nonimplanted (NI) control group. Within 3 d after birth, bulls assigned to the I treatment were implanted with 36 mg zeranol and reimplanted every 84 d until slaughter. Calves were weaned at 7.2 mo, preconditioned for 2 wk, and assigned within treatment to slaughter ages 12.0, 13.8, 15.7 and 17.4 mo. Blood samples were taken bimonthly from 8.3 to 16.6 mo of age. Weight gains, feed:gain ratios and slaughter and carcass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Hot carcass weight was 318.5, 320.2, 318.9, 323.8, 319.5, and 320.3 kg for the 36, 48, 60, 72, 84, and 96 mg zeranol doses, compared with 308.0 kg for ZEFUNOL EFFECTS ON STEER BONE AND SOFT TISSUE 3 controls. Gray et al (1986) found that bulls implanted with zeranol (36 mg) had a reduced percentage of bone in the 9-10-11 rib section, whereas Fumagalli et al (1989) found no effect of zeranol on the weight or percentage of bone in the carcasses of steers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hot carcass weight was 318.5, 320.2, 318.9, 323.8, 319.5, and 320.3 kg for the 36, 48, 60, 72, 84, and 96 mg zeranol doses, compared with 308.0 kg for ZEFUNOL EFFECTS ON STEER BONE AND SOFT TISSUE 3 controls. Gray et al (1986) found that bulls implanted with zeranol (36 mg) had a reduced percentage of bone in the 9-10-11 rib section, whereas Fumagalli et al (1989) found no effect of zeranol on the weight or percentage of bone in the carcasses of steers.…”
Section: Resultsmentioning
confidence: 97%
“…This is in contrast to the current study in which steers implanted with 24 mg or more of zeranol had 12% smaller ( P < ,051 external AP diameters than unimplanted controls. Gray et al (1986) found that bulls implanted with zeranol had reduced femur lengths and circumference. Increasing zeranol levels in the current study reduced ( P < .08) internal (marrow cavity) AP diameter linearly.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these substances, for example testosterone, zeranol, trenbolone acetate and allyl trenbolone had previously been used, some quite legally, as growth promoters or production enhancers, particularly in cattle (Patterson et al. , 1985; Baker & Gonyou, 1986; Gray et al. , 1986; Hunt et al.…”
Section: Violation Of Maximum Residue Limitsmentioning
confidence: 99%
“…There Unruh, Dikeman and Stevenson, 1986;Silcox, , 1987b E f f e c t s o f z e r a n o 1 o n reproduction in beef bulls: , , , . The highest zeranol concentration in reduced testis weight while mean epididymis any sample from the present study was weight was the same as for controls.…”
Section: The Vast Majority Of the Increase In Carcassmentioning
confidence: 99%